Laparoscopic Versus Open Surgery For Common Bile Duct Exploration - Ahmed, Shan E; Jahan, Yar; Khan, Muhammad Shahid (Biological and Clinical Sciences Research Journal, 2025)
Choledocholithiasis remains a common surgical problem, and the choice between laparoscopic and open common bile duct (CBD) exploration continues to influence perioperative outcomes. Minimally invasive laparoscopic CBD exploration (LCBDE) offers reduced postoperative morbidity and shorter recovery times compared to open surgery, but concerns persist regarding bile duct injury (BDI) and incomplete stone clearance, particularly in resource-limited settings such as Pakistan. Objective: To compare the intraoperative and postoperative outcomes of laparoscopic versus open CBD exploration in patients with choledocholithiasis. Methods: A descriptive comparative study was conducted at the Department of General Surgery, Bahawal Victoria Hospital, Bahawalpur, Pakistan, from November 23, 2024, to May 23, 2025. Fifty patients (aged 20–60 years, ASA ≤III) with imaging-confirmed choledocholithiasis were enrolled and divided equally into laparoscopic and open-surgery groups. Both procedures were performed by experienced consultant surgeons following standardized protocols. Intraoperative blood loss, postoperative bile drainage, hospital stay, residual stones, and CBD injuries were recorded. Data were analyzed using SPSS v26, applying Student’s t-test and Chi-square tests, with p < 0.05 considered statistically significant. Results: Baseline demographics, including age (mean 42.76 ± 9.65 vs 41.56 ± 9.27 years, p = 0.656) and BMI (26.39 ± 5.82 vs 25.92 ± 4.35 kg/m², p = 0.751), were comparable between open and laparoscopic groups. Laparoscopic exploration significantly reduced intraoperative blood loss (94.68 ± 19.95 mL vs 281.24 ± 30.73 mL; p < 0.001), postoperative bile drainage (179.25 ± 36.55 mL vs 326.92 ± 57.36 mL; p < 0.001), and hospital stay (3.96 ± 0.91 days vs 7.37 ± 1.59 days; p < 0.001). Residual stones were less frequent after laparoscopy (8% vs 32%; p = 0.034). The incidence of CBD injury was lower in the laparoscopic group (4% vs 24%; p = 0.042). Conclusion: Laparoscopic common bile duct exploration offers superior outcomes compared to open surgery, with reduced operative blood loss, fewer complications, shorter hospital stay, and higher stone-clearance rates. These findings support the broader adoption of laparoscopic techniques for choledocholithiasis management in Pakistan, emphasizing the need for enhanced laparoscopic training and resource allocation in tertiary-care settings.